BRAZILIAN BEEF : expansion in exports and international requirements - Carvalho Alves Paixão , Lucineide; Midori Yada de Almeida , Marcela (Revista Interface Tecnológica, 2020)
With the rapid progress and evolution that has been occurring in exports, in the last decades, the meat market has more than before established its sanitary and phytosanitary requirements and restrictions, the importance of correctly and safely meeting the standards established by importers. How the failure to comply with these standards directly and indirectly affects the export market and the countries' view of the quality, cleanliness and safety of our exported products. The greater the confidence regarding the quality of the product received, the greater the visibility that the exporting country will achieve abroad. For this reason, a bibliographic research was carried out to portray in this article, about this market that is constantly expanding, and the barriers it faces in view of the established norms.
Keywords: Sanitary and Phytosanitary Requirements; Growth.; Evolution